The design and conduct of Keep It Off: An online randomized trial of financial incentives for weight-loss maintenance. (February 2017) - Shaw, Pamela A; Yancy, William S; Wesby, Lisa; Ulrich, Victoria; Troxel, Andrea B; Huffman, David; Foster, Gary D; Volpp, Kevin
Background: Obesity continues to be a serious public health challenge. Rates are increasing worldwide, with nearly 70% of the US adults overweight or obese, leading to increased clinical and economic burden. While successful approaches for achieving weight loss have been identified, techniques for long-term maintenance of initial weight loss have largely been unsuccessful. Financial incentive interventions have been shown in several settings to be successful in motivating participants to adopt healthy behaviors. Purpose: Keep It Off is a three-arm randomized controlled trial that compares the efficacy of a lottery-based incentive, traditional direct payment incentive, and control of daily feedback without any incentive for weight-loss maintenance. This design allows comparison of a traditional direct payment incentive with one based on behavioral economic principles that consider the underlying psychology of decision-making. Methods: Participants were randomized in a 2:1 ratio for each active arm relative to control, with a targeted 188 participants in total. Eligible participants were those aged 30–80 who lost at least 11 lb (5 kg) during the first 4 months of participation in Weight Watchers, a national weight-loss program, with whom we partnered. The interventions lasted 6 months (Phase I); participants were followed for an additional 6 months without intervention (Phase II). The primary outcome is weight change from baseline to the end of Phase I, with the change at the end of Phase II a key secondary endpoint. Keep It Off is a pragmatic trial that recruited, consented, enrolled, and followed patients electronically. Participants were provided a wireless weight scale that electronically transmitted daily self-monitored weights. Weights were verified every 3 months at a Weight Watchers center local to the participant and electronically transmitted. Results: Using the study web-based platform, we integrated recruitment, enrollment, and follow-up procedures into a digital platform that required little staff effort to implement and manage. We randomized 191 participants in less than 1 year. We describe the design of Keep It Off and implementation of enrollment. Lessons Learned: We demonstrated that our pragmatic design was successful in rapid accrual of participants in a trial of interventions to maintain weight loss. Limitations: Despite the nationwide reach of Weight Watchers, the generalizability of study findings may be limited by the characteristics of its members. The interventions under study are appropriate for settings where an entity, such as an employer or health insurance company, could offer them as a benefit. Conclusions: Keep It Off was implemented and conducted with minimal staff effort. This study has the potential to identify a practical and effective weight-loss maintenance strategy.